2019
DOI: 10.1089/tmj.2018.0009
|View full text |Cite
|
Sign up to set email alerts
|

Key Characteristics for Successful Adoption and Implementation of Home Telehealth Technology in Veterans Affairs Home-Based Primary Care: An Exploratory Study

Abstract: Much remains to be done for effective HT integration in HBPC. Improving communication between HT and HBPC programs and establishing a system for identifying suitable patients for HT are vital. Future studies need to delineate operational processes and gather data on the added value of HT in HBPC to guide evidence-based integration of HT in VA and Medicare HBPC programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…A study on telehealth adoption among US hospitals showed that the rate of hospital telehealth is associated with differences in state policy [1]. The most common aspect of research is on an organisational level, i.e., telehealth adoption in hospitals [46] or among individuals from specific groups, such as older people [47][48][49]. As telehealth is considered at an individual level (clinician to clinician, clinician to patient), it is also connected with the health professional workforce andto some extendwith electronic health records [50].…”
Section: E-health Capacity Buildingmentioning
confidence: 99%
“…A study on telehealth adoption among US hospitals showed that the rate of hospital telehealth is associated with differences in state policy [1]. The most common aspect of research is on an organisational level, i.e., telehealth adoption in hospitals [46] or among individuals from specific groups, such as older people [47][48][49]. As telehealth is considered at an individual level (clinician to clinician, clinician to patient), it is also connected with the health professional workforce andto some extendwith electronic health records [50].…”
Section: E-health Capacity Buildingmentioning
confidence: 99%
“…Six studies 73–78 focused on technology—particularly telehealth—as a way to extend the reach of HBPC. Dang and colleagues reported that 76% of surveyed VHA HBPC practices used remote biometric monitoring and messaging devices.…”
Section: Resultsmentioning
confidence: 99%
“…71 Shafir noted that caregivers enjoyed greater peace of mind when they could rely on competent homebased medical care. 69 Telehealth Six studies [73][74][75][76][77][78] focused on technology-particularly telehealth-as a way to extend the reach of HBPC. Dang and colleagues reported that 76% of surveyed VHA HBPC practices used remote biometric monitoring and messaging devices.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic, such VVs were already a viable method for performing ambulatory office-based care remotely, particularly in the period following hospital discharge, with a trend toward lower noshow rates compared to traditional visits among HF patients 28 . Virtual VVs are also demonstrably effective among Veterans Affairs patients 29 . In fact, the VA has served as a key pioneer for telehealth advancements well prior to the COVID-19 era.…”
Section: History and Remote Physical Examination During Telemedical Vmentioning
confidence: 96%